2015
DOI: 10.1093/femspd/ftv036
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Francisella tularensis Schu S4 defined mutants as live-attenuated vaccine candidates

Abstract: Francisella tularensis (Ft), the etiological agent of tularemia and a Tier 1 select agent, has been previously weaponized and remains a high priority for vaccine development. Ft tularensis (type A) and Ft holarctica (type B) cause most human disease. We selected six attenuating genes from the live vaccine strain (LVS; type B), F. novicida and other intracellular bacteria: FTT0507, FTT0584, FTT0742, FTT1019c (guaA), FTT1043 (mip) and FTT1317c (guaB) and created unmarked deletion mutants of each in the highly hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…Vaccination with LVS effectively prevents laboratory-acquired infection, but studies on volunteers have revealed that it affords only marginal protection against aerosol infection (Saslaw et al, 1961a,b; Burke, 1977). It was hypothesized that it would be possible to generate a superior F. tularensis vaccine and we and others have generated a number of targeted mutants of SCHU S4 and their efficacy has been evaluated using in vivo models with virulent F. tularensis strains (Kadzhaev et al, 2009; Conlan et al, 2010; Shen et al, 2010; Ryden et al, 2012; Santiago et al, 2015). In particular one mutant, Δ clpB , was found to confer superior efficacy to LVS, as demonstrated by survival after infection with SCHU S4 (Conlan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination with LVS effectively prevents laboratory-acquired infection, but studies on volunteers have revealed that it affords only marginal protection against aerosol infection (Saslaw et al, 1961a,b; Burke, 1977). It was hypothesized that it would be possible to generate a superior F. tularensis vaccine and we and others have generated a number of targeted mutants of SCHU S4 and their efficacy has been evaluated using in vivo models with virulent F. tularensis strains (Kadzhaev et al, 2009; Conlan et al, 2010; Shen et al, 2010; Ryden et al, 2012; Santiago et al, 2015). In particular one mutant, Δ clpB , was found to confer superior efficacy to LVS, as demonstrated by survival after infection with SCHU S4 (Conlan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These observations further indicated that, in most cases, antibacterial activity does not result from the inhibition of FtIMPDH. Second, we determined the antibacterial activities of 10 compounds against the ΔguaB strain of F. tularensis Schu S4 (17), which lacks the gene encoding FtIMPDH and requires the presence of guanine for growth. These bacteria should be resistant to FtIMPDH inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The MIC was defined as the lowest drug concentration at which the growth was inhibited at least 90% compared to that of the positive control. The ΔguaB strain (FTT1317c) (17), which lacks FtIMPDH, was always grown in the presence of guanine (10 g/ml). The MBC was determined by plating 5 l of culture from each well on a Mueller-Hinton agar (MHA) plate and incubating it at 37°C for 2 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that vaccine candidates derived from subsp. tularensis with deletions in a series of targeted genes, including guaB and guaA genes, did not confer protection in the mouse model [9]. In this study, we have targeted another critical metabolic pathway by engineering three novel live attenuated vaccine candidates, Schu S4ΔaroC, Schu S4ΔaroD, and Schu S4ΔaroCΔaroD.…”
Section: Introductionmentioning
confidence: 99%